Coagulation factor IV is an indicator of symptomatic pulmonary embolism in patients with primary lung cancer. (9th December 2019) - Xiong, Wei; Zhao, Yunfeng; Xiong, Yifan; Xu, Mei; Pudasaini, Bigyan; Du, He; Guo, Xuejun
Abstract: Background: Coagulation factor IV, also known as serum ionised calcium (SIC), participates in coagulative process and tends to elevate in patients with primary lung cancer. It may be an indicator of symptomatic pulmonary embolism (PE) due to primary lung cancer (LC). Methods: A total of 388 patients who underwent CTPA and/or radionuclide ventilation perfusion scanning due to PE‐suspected symptoms were stratified into LCPE (lung cancer and PE) group ( n  = 95), PE group ( n  = 99), LC group ( n  = 98) and control group ( n  = 96). At admission, the level of SIC and STC (serum total calcium) was compared among four groups. At discharge, the level change of SIC and STC from admission to discharge was compared among four groups. The coefficients analysis between SIC as well as STC and the possibility of PE were performed. Results: The SIC of LCPE group was the highest among four groups at admission ( P  < 0.001). The level change of SIC from admission to discharge in LCPE group was the highest among four groups ( P  = 0.001). A ROC curve analysis demonstrated that the sensitivity and specificity of SIC for a diagnosis of PE among LC patients were 71.9% and 86.0%, respectively. The area under curve (AUC) was 0.781. Along with the increase of 0.1 mmol/L in SIC level, the risk ratio for a PE was 2.165 (1.537‐2.849) ( P  < 0.001). Conclusions: Serum ionised calcium may be an indicator of pulmonary embolism in patients with primary lung cancer.